2019
DOI: 10.3390/molecules24173116
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Constituents Affecting the Secretion of Pro-Inflammatory Cytokines in LPS-Induced U937 Cells by UHPLC-HRMS-Based Metabolic Profiling of the Traditional Chinese Medicine Formulation Huangqi Jianzhong Tang

Abstract: Within non-communicable diseases, chronic inflammatory conditions represent one of the biggest challenges for modern medicine. Traditional Chinese Medicine (TCM) has been practiced over centuries and has accumulated tremendous empirical knowledge on the treatment of such diseases. Huangqi Jianzhong Tang (HQJZT) is a famous TCM herbal formula composed of Radix Astragali, Ramulus Cinnamomi, Radix et Rhizoma Glycyrrhizae Praeparata cum Melle, Radix Paeoniae Alba, Rhizoma Zingiberis Recens, Fructus Jujubae and Sac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
2
13
0
1
Order By: Relevance
“…In our future report, we aim to show the multi-ion channel mechanism of DFD. In addition, with the development of mass spectrometry, multiple constituents of the components of DFD have been analyzed and characterized in recent years [29][30][31][32][33][34]. Modern pharmacological studies have shown that the components of DFD have anti-inflammatory [35][36][37][38][39], antioxidative stress [40][41][42], and myocardial protection [42][43][44][45] effects.…”
Section: Discussionmentioning
confidence: 99%
“…In our future report, we aim to show the multi-ion channel mechanism of DFD. In addition, with the development of mass spectrometry, multiple constituents of the components of DFD have been analyzed and characterized in recent years [29][30][31][32][33][34]. Modern pharmacological studies have shown that the components of DFD have anti-inflammatory [35][36][37][38][39], antioxidative stress [40][41][42], and myocardial protection [42][43][44][45] effects.…”
Section: Discussionmentioning
confidence: 99%
“…T33 is a traditional Chinese formula that consists of five traditional Chinese medicines including Gansui (Kansui Radix), Zhigancao (Glycyrrhizae Radix et Rhizoma Praeparata cum Melle), Baishao (Paeoniae Radix Alba), Jiangbanxia (Pinelliae Rhizoma Praeparatum Cum Zingibere et Alumine), and Dahuang (Rhei Radix et Rhizoma). 21 , 27 , 28 T33 were provided by DeYi Chinese Medicine Clinic (Changhua, Taiwan). Briefly, a total of 32 g mixture of Gansui, Dahuang, Baishao, Jiangbanxia, and Zhigancao was mixed in a ratio of 3:2:12:6:9.…”
Section: Methodsmentioning
confidence: 99%
“…Anti-oxidation Sil and Chakraborti, 2016;Carnovali et al, 2019;Cheng et al, 2020a;Alzahrani et al, 2020;Baek et al, 2020; 7. Anti-inflammation Carnovali et al, 2019;Nöst et al, 2019;Cheng et al, 2020a;Alzahrani et al, 2020;Baek et al, 2020) 8. Osteoporosis (Rho et al, 2017;Carnovali et al, 2019;Carnovali et al, 2020) 9.…”
Section: Sorting Of Traditional Effects and Modern Pharmacological Re...unclassified